SELF-ACTUALIZATION APPLICATION IN HELPING HUMAN CHARACTER DEVELOPMENT BASED ON FLORENCE LITTAUER PERSONALITY TEST BASED ON ANDROID - Tangguh Destio Pramono; Guntur Eka Saputra; Josephine Haneta Excelentia Savitri Dinarbrata; Haikal Ardikatama; Sinatrio Bimo Wahyudi; Adam Rozaq Sobari (International Journal Science and Technology, 2023)
A midlife crisis is a stage when a person feels anxious, worried, and confused about their purpose in life. This condition occurs when a person currently doubts their future and quality of life. The quarter-life crisis phase can be overcome with better self-awareness, better self-awareness and appreciation, and increased user productivity. Therefore, self-realization is the right solution to survive the Quarter Life crisis. Self-actualization (selftuazion) offers several interesting features tailored to the needs of users in self-actualization, such as self-assessment, ToDo application and statistics, interesting articles, self-introduction pages, motivational quotes, and reminder notifications to help in the process of loving yourself. The results of the pilot test on 22 target group respondents showed that the functions contained in Selftuazion had a good effect on respondents in overcoming the problem of Quarter Life Crisis. This application produces 20 pages with features that are in accordance with self-actualization, based on the results of testing with users that the application can be used properly and get a score of 88 in the acceptable category with grade B or Good.